A Reflection on the Liminal Position of Man Based on the Imaginative Faculty in Al-Farabi and Kant - Yusof Shaghool; Mohammad Khalili (حکمت سینوی)
In Islamic tradition, man is defined as an intermediary and liminal being, situated between the animal and the angel, with the constant potential for ascent or descent to either of these ontological spheres. This paper endeavors to provide a philosophical interpretation of this intermediary and liminal position of man based on the concept of the imaginative faculty in the philosophies of Al-Farabi and Kant. The central question of this essay is to examine how, in the works of these two philosophers, epistemology serves as a platform for offering an ontological interpretation of man's liminal position. This paper represents an initial exploration of this topic. Given the prominence of the imaginative faculty in Kant's philosophy, particularly in his discussion of transcendental deduction, this paper will begin by tracing the trajectory of transcendental deduction, highlighting the role of the imaginative faculty and its two levels of productive and reproductive imagination. It will then proceed to examine these two levels of imagination (productive and reproductive) in Al-Farabi's thought, without resorting to simplistic comparisons or equating the two philosophers' perspectives. Employing an analytical approach, the paper will seek to establish an anthropological foundation for the imaginative faculty in the philosophies of both thinkers. The intermediary role of imagination in the realization of knowledge in the works of these two philosophers provides the basis for such an endeavor.